Genetic variation at the FTO locus influences RBL2 gene expression - Jowett, J.; Curran, J.; Johnson, M.; Carless, M.; Göring, H.; Dyer, T.; Cole, S.; Comuzzie, A.; MacCluer, J.; Moses, Eric; Blangero, J. (CMP Media LLC, 2010)
OBJECTIVE - Genome-wide association studies that compare the statistical association between thousands of DNA variations and a human trait have detected 958 loci across 127 different diseases and traits. However, these statistical associations only provide evidence for genomic regions likely to harbor a causal gene(s) and do not directly identify such genes. We combined gene variation and expression data in a human cohort to identify causal genes. RESEARCH DESIGN AND METHODS - Global gene transcription activity was obtained for each individual in a large human cohort (n = 1,240). These quantitative transcript data were tested for correlation with genotype data generated from the same individuals to identify gene expression patterns influenced by the variants. RESULTS - Variant rs8050136 lies within intron 1 of the FTO gene on chromosome 16 and marks a locus strongly associated with type 2 diabetes and obesity and widely replicated across many populations. We report that genetic variation at this locus does not influence FTO gene expression levels (P = 0.38), but is strongly correlated with expression of RBL2 (P = 2.7 × 10-5), ~270,000 base pairs distant to FTO. CONCLUSIONS - These data suggest that variants at FTO influence RBL2 gene expression at large genetic distances. This observation underscores the complexity of human transcriptional regulation and highlights the utility of large human cohorts in which both genetic variation and global gene expression data are available to identify disease genes. Expedient identification of genes mediating the effects of genome-wide association study - identified loci will enable mechanism-of-action studies and accelerate understanding of human disease processes under genetic influence. © 2010 by the American Diabetes Association.